Comparative welfare state politics : development, opportunities, and reform - Kersbergen, Kees van, 1958- (Cambridge University Press, 2014)
"Kees van Kersbergen and Barbara Vis explain the political opportunities and constraints of welfare state reform in advanced democracies"--